1982
DOI: 10.1113/jphysiol.1982.sp014304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamate, aspartate and related derivatives on cerebellar Purkinje cell dendrites in the rat: an in vitro study

Abstract: SUMMARY1. The responses ofPurkinje cells to short duration (pulse) ionophoretic applications of L-aspartate (L-asp), L-glutamate (L-glu), N-methyl DL-aspartate (NMDLA) and quisqualic acid in their dendritic fields were studied in vitro on sagittal slices of lobules IX and X of the adult rat cerebellum.2. Pulse application of L-asp or L-glu evoked transient and dose-dependent increases in the firing rate of the simple spikes recorded extracellularly as single units. When the ionophoretic electrode was positione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

1985
1985
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(60 citation statements)
references
References 30 publications
5
54
1
Order By: Relevance
“…This is further supported by the existence of an NMDA-mediated component in the CF-EPSC. However, considerable previous evidence indicated that NMDA-Rs are not, or very weakly, expressed by adult Purkinje cells (Crepel et al, 1982;Garthwaite et al, 1987;Konnerth et al, 1990;Krupa and Crepel, 1990;Farrant and Cull-Candy, 1991;Llano et al, 1991). If this is true, the NMDA-mediated CF-EPSC evidenced here has to be of presynaptic origin.…”
Section: Cf-epscs Display An Nmda Componentmentioning
confidence: 83%
“…This is further supported by the existence of an NMDA-mediated component in the CF-EPSC. However, considerable previous evidence indicated that NMDA-Rs are not, or very weakly, expressed by adult Purkinje cells (Crepel et al, 1982;Garthwaite et al, 1987;Konnerth et al, 1990;Krupa and Crepel, 1990;Farrant and Cull-Candy, 1991;Llano et al, 1991). If this is true, the NMDA-mediated CF-EPSC evidenced here has to be of presynaptic origin.…”
Section: Cf-epscs Display An Nmda Componentmentioning
confidence: 83%
“…Tendril collaterals of climbing fibers project to Purkinje cell bodies near their axons (Palay and Chan-Palay, 1974). Physiological studies have demonstrated that glutamate or aspartate from parallel fibers acts on NMDA receptors located on basket cell dendrites to increase GABA release, because the application of NMDA onto adult cerebellar Purkinje cells produces inhibitory responses that are blockable by bicuculline (Crepel et al, 1982;Quinlan and Davies, 1985;Llano et al, 1991). Climbing fiber tendril collaterals near NMDA receptors on basket cell axons could mediate a similar response.…”
Section: Ontogenic Roles Of D-serine In the Cerebellummentioning
confidence: 99%
“…Moreover, the present study revealed that glutamate-induced vasoconstrictions are insensitive to NMDA receptor antagonism. Finally, Purkinje cells do not express functional NMDA receptors (Crepel et al, 1982), and, in contrast to glutamate, NMDA does not stimulate arachidonic acid release from astrocytes (Stella et al, 1994). Therefore, slices were stimulated with NMDA to assess the contribution of endogenously released neuronal NO in cerebellar dilation.…”
Section: Nmda-induced Vasodilationmentioning
confidence: 99%
“…We found a greater release of NO in slices stimulated with glutamate compared with NMDA, indicating activation of non-NMDA receptors in the glutamate-induced NO release. Indeed, stellate cells, which express NMDA receptors (Rancillac and Crepel, 2004) whereas Purkinje (Crepel et al, 1982) and glial (Stella et al, 1994) cells do not, also express Ca 2ϩ -permeable AMPA receptors (Liu and Cull-Candy, 2000) and group I mGluRs (Grandes et al, 1994;Karakossian and Otis, 2004), and their concurrent activation by glutamate most likely explains, at least in part, the larger amounts of NO released by glutamate compared with NMDA. Yet, this larger NO release translated into cerebellar constrictions and not dilations, suggesting that the constriction elicited by the synthesis and release of contractile arachidonic acid derivatives from glia and/or neurons and of endothelin-1 from Purkinje cells predominates over the NO-induced dilation (Fig.…”
mentioning
confidence: 99%